We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
152
1
avatar

Someone please help me with this! Ive been stuck on this problem. 

 

https://learning.k12.com/content/enforced/518567-COF_ID162535/Algebra%202%20Unit%2011.pdf?_&d2lSessionVal=Wou1ym05YuhH6ilerroNfuBSq

 Feb 1, 2019
 #1
avatar+7712 
+1

\(f(x) = x^2-6x+8, g(x) = x-2\)

x f(x) g(x)
0 8 -2
1 3 -1
2 0 0
3 -1 1
4 0 2
5 3 3
6 8 4

You see that when x = 2, f(x)=g(x)=0 and when x = 5, f(x)=g(x)=3.

 

So f(x) = g(x) when x = 2 and x = 5.

 Feb 1, 2019

27 Online Users

avatar